(3WHbGJ GdabgGA GdTGaYjIs - (3GHf GdUdGM , YKeGf Hf YHO GdQMef Hf YKeGf Hf ehSi Hf CHj GdfUQ GdfUQj GdTgQRhQj GdcQOj GdTQNGfj, Jbj GdOjf CHh YeQh, GHf GdUdGM,J (B643 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Cced GdMeO hdG Edg EdG Gddg CeG HYO aEf eYQaI GdEfSGf HCMhGd GdYdeGA SaYI hRjf s
(3BNQgG (B:s
(3ef HGH GdfSH (B: (3fXGe Gdedc GdhRjQ (B: (3gh CHh Ydi GdMSf Hf Ydi Hf ESMGb GdYHGS , SHb BNQ cJGH GdWHbGJ s
(3HgG fXGe GdJYbjHIs
(3QJHI GdeDda Ydi MQha GdeYLes
(3JHUQI GdYfhGf (B:s
(3GNJUGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B207 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B257s
Keywords: (3GdJGQjNs